From vision to reality: transforming the social justice vision of the Partai Keadilan Sejahtera (PKS) into development policy in West Sumatra, Indonesia - Mulyawan, Fitra; Efendi, Faisal; Afrinal, Afrinal; Majid, Ikhwanuddin Abdul (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This research aims to analyze the social justice vision of the Partai Keadilan Sejahtera (PKS) in the development policy of the West Sumatra government. This research is conducted in West Sumatra Province, selected as the research location considering that West Sumatra is known for its strong adherence to Islamic teachings and the homogeneity of its social and cultural life. Significant development policies in West Sumatra. This research examines three main aspects, namely the implementation of the vision of social justice, its derivative programs, and implementation barriers. This research uses descriptive-analytical methods through literature studies, document analysis, and interviews. The results showed the transformation of PKS's vision into the West Sumatra government's development policies through a strategic framework based on religion, politics, economics, and socio-community, with a holistic strategy that integrates Islamic values and local culture through religious da'wah, education, and community empowerment, especially in the economic sector that focuses on equitable development, income equality, Although the research findings also reveal obstacles in the form of a lack of synergy and collaboration in implementation, overall PKS has succeeded in utilizing religion and culture as a transformative instrument to realize social justice in West Sumatra.